The Relationship Between Self-Regulated Learning, Family Support and Learning Motivation on Students’ Learning Engagement - Azhari, Septian Cahya; Siti Fadjarajani; Ely Satiyasih Rosali (LPPM Undiksha, 2023)
Students' learning engagement grows from students' awareness of the importance of participating in the learning process, this is shaped by learning motivation, self-regulation, support from the family environment as well as the school. This study analyze the relationship between self-regulated learning, family support and learning motivation to students' learning engagement. A total of 100 of 12 grade students at senior high school participated to fill out the questionnaire in this study. Structural equation modeling partial least square (SEM-PLS) is used as a tool to analyze the complex relationships of these variables. Reflective analysis of variables is used to statistically explore the relationships between variables. The P values between variables significantly indicate that there is a relationship between FS ->LM (0.006), LM->LE (0.000), SRL->LE (0.006), and SRL->LM (0.000). Based on the results of this study,: (1) parental and teacher support has an important role in shaping student learning motivation, (2) student self-regulated learning is formed by the student's learning environment and students' own awareness, and (3) learning engagement is influenced by SRL, family support and student internal motivation. It is hoped that the results of this study can help parents and teachers to create a conducive learning environment for students both at home and at school.